Pengaruh Penerapan Akuntansi Sektor Publik dan Kualitas Laporan Keuangan Terhadap Akuntabilitas Kinerja Instansi Pemerintah Pada Satuan Kerja Perangkat Daerah Kabupaten Deli Serdang - Ilmi Rafarni Gea (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2021)
This study was conducted to determine: (1) The Effect of Public Sector Accounting Implementation on Performance Accountability of Government Agencies in SKPD in Deli Serdang Regency. (2) The Effect of Financial Report Quality on Performance Accountability of Government Agencies at SKPD in Deli Serdang Regency. (3) The Effect of Public Sector Accounting Implementation and Quality of Financial Reports on Performance Accountability of Government Agencies at SKPD in Deli Serdang Regency. The data collection method used in this study was a questionnaire. The population in this study were 95 employees at SKPD SKPD in Deli Serdang Regency who were still actively working. The questionnaire was tested for validity and reliability before collecting research data. The analysis prerequisite test includes instrument test and classical assumption test which includes normality test, multicollinearity test, heteroscedasticity test and linearity test. The data analysis method used is multiple regression analysis. The results of this study are: (1) The application of Public Sector Accounting has a significant positive effect on the Performance Accountability of Government Agencies (2) The Quality of Financial Reports has a positive and significant effect on the Performance Accountability of Government Agencies (4) The Implementation of Public Sector Accounting and the Quality of Financial Reports has a significant influence significant to the Performance Accountability of Government Agencies.